Needs Analysis for Developing an SDG 14 (Life Below Water) Big Book to Support Preschoolers’ English Learning through Shared Reading - Ni Nyoman Anti Prianti; Putu Kerti Nitiasih; Ni Wayan Monik Rismadewi (Yayasan Zia Salsabila, 2026)
In early childhood education, English language learning played an important role in developing children’s early literacy skills. This study aimed to analyze the need for developing an SDG 14 (Life Below Water)-based Big Book to support preschool children’s English learning through shared reading activities at PAUD Pelita Kasih Singaraja. The study employed a descriptive qualitative method involving classroom observations and semi-structured interviews with the English teacher of Class A2. The findings indicated that current teaching practices had not fully supported children’s early literacy development due to a lack of engaging and effective learning materials. Although teachers used strategies such as questioning, repetition, and picture guessing, student engagement tended to decline as the lesson progressed. The use of media such as flashcards and small storybooks was insufficient to sustain children’s interest and support meaningful shared reading activities. Furthermore, environmental education related to SDG 14 (Life Below Water) had not been effectively integrated into shared reading activities. Teachers expressed positive views regarding the development of SDG 14-based Big Books, as they could enhance student engagement, support shared reading activities, and build environmental awareness.